THE POTENTIAL OF PROBIOTICS AS AMMONIA LEVELING AGENT IN EXCRETE WASTE IN BROILER CHICKEN LIVESTOCK - Hendrawan Hendrawan (Journal of Livestock Science and Production, 2023)
Broiler chicken (Gallus sp.) is non ruminant animal being domesticated for the purpose being harvested for its meat. Broiler chicken is generally used as commodity of poultry farm because producing meat that can be harvested in short time in range of 30 (thirty) days. This research purpose is to understand about bacterial potency that used as ammonia reducing agent in manure waste that can be applicated in poultry farm for broiler chicken. The method used in this research is literature study in related theme with research object. The bacteria used in this research is Lactobacillus acidophilus, Lactobacillus bulgaricus, Lactobacillus plantarum, Bacillus cereus, Bacillus amyloliquefaciens, Lactobacillus sp. and Bacillus sp. The usage of bacteria is as probiotic agent that can be applied in excrete waste in broiler chicken in poultry farm of broiler chicken. The result expected is that bacteria agent can effectively reducing ammonia concentration in excrete of broiler chicken. The conclusion of this research is that bacteria agent can reduce the amount of ammonia concentration in excrete waste of poultry farm for broiler chicken (Gallus sp.).